COMPARATION OF EFFECTIVENESS OF SILVER SULFADIAZINE AND GENTAMICIN ON ABRASION WOUND HEALING - Mohan, Mohan; Jailani, Muhammad; Amirsyah, Mirnasari (Jurnal Rekonstruksi dan Estetik, 2019)
Highlights: Silver sulfadiazine (SSD) in abrasion wound treatment giving the advantages in proliferation phase. SSD was found to be more effective in healing abrasions than gentamicin cream. Abstract: Introduction: Abrasion is injury to skin due to trauma that affects the surface of the epidermis or superficial epithelium, especially from friction to the depth of the dermal papillae. The basic principle of abrasion treatment is to maintain moist condition in wound surface.This study aims to compare the effectiveness of silver sulfadiazine (SSD) and gentamicin cream in the process of healing abrasions. Methods: The study used a post-test only control group design. A total of 30 samples of abrasion patients who came for treatment at the ED were sampled, and divided into 3 groups, namely wound care by providing SSD, gentamicin and tulle. Results: The wound dimensions are assessed from the length and width measured at the 1st day, the 5th day, and the 10th day. At the 10th day assessment, SSD was found to be more effective in healing abrasions compared to other groups. Conclusions: The use of SSD in abrasion wound treatment is believed to have advantages in proliferation phase where SSD is a sulfonamide class antibiotic that produces synergic effects along with silver which constantly absorbs exudates and bacteria, combines chloride tissue and several other proteins in the process of wound healing.